Effect of Nitrogen-Based Ion Implantation on The Characteristics of 316L Stainless Steel for Implant Materials - Rudyardjo, M.Si., Drs. Djony Izak; Ikhsan, Firman Maulana; Supardi, Adri (Universitas Airlangga, 2022)
The effect of nitrogen-based ion implantation on the characteristics of 316l stainless steel for implant materials has been performed. This study aims to determine the effect of variations in implantation energy on the characteristics of the surface mechanical properties, density, and corrosion resistance of 316L stainless steel. The 316L stainless steel plate was implanted with nitrogen ions with an optimum dose of 5 x 1016 ions/cm2 for various implantation energies of 70, 75, 80, 85, and 90 keV. The implanted samples were then characterized by density, hardness, corrosion resistance, and microstructure tests using SEM-EDX. The test results showed an increase in hardness and corrosion resistance in pieces implanted with nitrogen ions and reached the optimum point at an implantation energy of 80 keV. This was also supported by the results of the SEM-EDX analysis, which showed an addition of nitrogen content from the maximum limit of the ASTM 2000 standard for 316L stainless steel of 0.1% to 2.2%. Whereas in the density test, the density of the material tends to be constant at the energy variations carried out but has increased after implantation.